Eye‐tracking for longitudinal assessment of social cognition in children born preterm. (29th July 2020) - Dean, Bethan; Ginnell, Lorna; Ledsham, Victoria; Tsanas, Athanasios; Telford, Emma; Sparrow, Sarah; Fletcher‐Watson, Sue; Boardman, James P.
Abstract : Background and objectives: Preterm birth is associated with atypical social cognition in infancy, and cognitive impairment and social difficulties in childhood. Little is known about the stability of social cognition through childhood, and its relationship with neurodevelopment. We used eye‐tracking in preterm and term‐born infants to investigate social attentional preference in infancy and at 5 years, its relationship with neurodevelopment and the influence of socioeconomic deprivation. Methods: A cohort of 81 preterm and 66 term infants with mean (range) gestational age at birth 28 +5 (23 +2 –33 +0 ) and 40 +0 (37 +0 –42 +1 ) respectively, completed eye‐tracking at 7–9 months, with a subset re‐assessed at 5 years. Three free‐viewing social tasks of increasing stimulus complexity were presented, and a social preference score was derived from looking time to socially informative areas. Socioeconomic data and the Mullen Scales of Early Learning at 5 years were collected. Results: Preterm children had lower social preference scores at 7–9 months compared with term‐born controls. Term‐born children's scores were stable between time points, whereas preterm children showed a significant increase, reaching equivalent scores by 5 years. Low gestational age and socioeconomic deprivation were associated with reduced social preference scores at 7–9 months. At 5 years, preterm infants had lower Early Learning Composite scores than controls, but this was not associated with social attentional preference in infancy or at 5 years. Conclusions: Preterm children have reduced social attentional preference at 7–9 months compared with term‐born controls, but catch up by 5 years. Infant social cognition is influenced by socioeconomic deprivation and gestational age. Social cognition and neurodevelopment have different trajectories following preterm birth.